Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Siswa Kelas VIII SMP Negeri Wederok 3 Tahun Ajaran 2021/2022 - Robertus Leonardus Nahak; Antonius Bere; Yuditha Sofiana Kofi (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
This research aims to discuss the influence of the Problem Based Learning Model on the Learning Outcomes of Class VIII Students at Wederok State Middle School. The method used in this research is Classroom Action Research. The results of this research are that an average of 51 students is converted into 4 categories, so the average score of learning outcomes for Wederok State Middle School students after learning using the Problem Based Learning (PBL) learning model is generally in the not good category. Based on the results of research conducted in cycle I and cycle II with the application of the Problem Based Learning (PBL) learning model, learning outcomes have increased. This can be seen from the increase in the average student score during the research, namely 51 in cycle I and 85 in cycle II.